The Function of Islamic Boarding School as a Driver of Social Change: Case Study of Mamba'ul Ishlah Islamic Boarding School in East Lampung - Khaerul Umam; Husni Mubarok (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
The habit of getting drunk and gambling rampant in the Cirebon Baru hamlet is a general problem faced by the community in Indonesia. This habit is considered a negative one because it contradicts the norms that the community has agreed upon. This negative behavior changed with the birth and development of the Mamba'ul Ishlah Islamic boarding school, driven by several religious leaders. This article aims to analyze the structural functionalism process carried out by the boarding school through its religious leaders so that it can change the social system of the community in a more positive direction. Through a case study approach, this article explains in an analytical descriptive manner. The theory used to analyze the case is Talcott Parson's structural functionalism which includes adaptation, goal attainment, integration, and latency pattern. This article found two important things related to the role of Islamic boarding schools in social change in the community, namely the cultural part by taking a more persuasive and intimate approach, namely by cutting the communication distance with the community through the tradition of jagongan and jokes. Second, the structural role is by utilizing the increasing social status of religious leaders so that they have complete legitimacy to direct the community in a more positive direction, namely the perpetuation of spiritual routines such as yasinan, istighotsah, shalawat assemblies, and yellow book recitation.